Isaiah's daughter : a novel of prophets & kings - Andrews, Mesu, 1963- (WaterBrook, 2018)
"In this epic Biblical narrative, ideal for fans of The Bible miniseries, a young woman taken into the prophet Isaiah's household rises to capture the heart of the future king. Isaiah adopts Ishma, giving her a new name--Zibah, delight of the Lord--thereby ensuring her royal pedigree. Ishma came to the prophet's home, devastated after watching her family destroyed and living as a captive. But as the years pass, Zibah's lively spirit wins Prince Hezekiah's favor, a boy determined to rebuild the kingdom his father has nearly destroyed. But loving this man will awake in her all the fears and pain of her past and she must turn to the only One who can give life, calm her fears, and deliver a nation. "Andrews (The Pharaoh's Daughter) offers her unique brand of in-depth Bible knowledge and storytelling flair... [she] is gifted at bringing the past to life..."--Publishers Weekly (starred review)"--